Screening and monitoring of diabetic polyneuropathy in clinical practice: present and future with connected devices - Lefaucheur, Jean-Pascal (Frontiers in Neurology, 2025)
New perspectives are opening up today in the management of diabetes thanks to the possibility of measuring, over long periods in daily life, different biomarkers likely to improve glycaemic control, such as continuous glucose monitoring and time-in-range assessment. This is part of personalized medicine. There is therefore a challenge to also benefit from specific biomarkers in the prevention and monitoring of polyneuropathy in diabetics, one of the most common type of peripheral nerve disorder worldwide. This is now possible with the development of connected tools, allowing for example to monitor at home the evolution of skin temperature or conductance at the level of the feet. In this article, the current use and recent advances in laboratory tools for the early diagnosis and objective monitoring of diabetic polyneuropathy and its progression will be presented. The follow-up of neuropathies will undoubtedly be significantly modified in clinical practice in the future, particularly in the context of diabetes, thanks to the use of connected tools and remote monitoring.